GIs, a promising innovation for the development of Africa's food systems? The decisive role of collective actions - (:unkn) unknown (My University, 2024)
The emergence of geographical indications (GIs) in the Global South, particularly in Africa, has sparked political interest due to their potential as a development tool. GIs are perceived as important innovations within food systems, which lead to changes in how actors coordinate within the sector and the territory. These new forms of coordination can generate positive economic impacts across various scales. Drawing on theories of change, the commons and collective action, this article seeks to highlight the importance of collective actions to these potential economic impacts, as collective action is notably necessary to manage the common resource that is the collective reputation of GIs. The analysis of economic impacts of GIs in in the Global South through literature reviews shows that the institutionalization of the collective reputation management through GIs does not guarantee economic impacts on the one hand, and on the other hand, that it generates mixed economic impacts within the production system, value chain, and territory. The in-depth analysis of the mechanism underlying these economic impacts of GIs, which resulted in modeling an impact pathway of GIs, shows that the success of collective actions (CAs) is fundamental to the realization of the expected impacts. This success is explained by numerous factors, analyzed in the article, that vary depending on the impacts they contribute to. In delving into GIs in in the Global South, various constraints such as the top-down approach in GI implementation that inadequately involves upstream stakeholders in the GI process, and the heterogeneity of actors shaping rules in terms of resources and power, hinder the success of these CAs and consequently the success of GIs.
Keywords: African Research